Energy Transition - Gamio Aita, Pedro (2018)
The country has a commitment, which springs up in 2015 Paris Treaty, to reduce its emissions. Therefore, it must stop deforestation and accelerate a gradual change in the energy matrix, go efficiently towards clean energies and achieve sustainable decentralized growth. Governance and the capacity to face climate change are at stake: this is the urgency of a new energy policy. This effort must have strategic planning with short, medium and long term goals: Peru building its own energy transition. Peru faces a great challenge. A society that seeks its development must handle with extreme care and prudence the renewable and non-renewable natural resources within its reach, as well as the human factor and the cultural and social aspects linked to the management of resources. A first step in this task is environmental literacy and strategic planning in the formulation of public policies to promote sustainable growth of economic activities. In Peru, we need to empower people and articulate public social and economic policies, build links in favor of a healthy environment and sustainable development.